An undergraduate peer mentoring program at a Canadian university: Impact on student learning as perceived by instructors, peer mentors, and students - Petrescu, Dan S.; Yazdani, Armin; VanderSchee, Cassidy R.; Bailey, Christopher A.; Covens, Faygie; Harpp, David N. (International Journal for Students as Partners, 2021)
Large undergraduate courses make it difficult for students to achieve learning outcomes, in part due to the lack of resources available to course instructors to support student learning in these intimidating and often impersonal settings. One way to support instructor teaching and student learning is the implementation of undergraduate peer mentoring programs, which capitalize on the Students-as-Partners framework. Undergraduate mentors’ relatability to their peers and their mastery of the course content make them excellent resources. This paper describes the development and implementation of a university-wide undergraduate peer mentoring program at McGill University in Canada and its impact on student learning as perceived by three populations: instructors, peer mentors, and students. Data on perceived learning was gathered through qualitative surveys. This case study presents one implementation model that may guide and inform the implementation of similar programs at other higher education institutions.